Giant adrenal gland pseudo-cyst: a case report with literature review - Muhammad Nasir; Rana Arslan Rabbani; Hamza Hamdullah; Qadri, Haseeb Mehmood (Journal of the Pakistan Medical Association, 2023)
Adrenal Gland Cysts are rare among all the pathologic cysts that occur in human beings; the pseudo-cyst variety even rarer. Adrenal pseudo-cysts are asymptomatic, non-functional, small, and incidentally discovered disease entities. Their clinical presentation is usually the result of their mass effects. Thanks to the advanced diagnostic technology, more such cases are being discovered timely and managed surgically, before life-threatening complications occur. Open surgical treatment remains the treatment of choice for giant cysts. Keywords: Adrenal Gland Cyst, Pseudo-, Lumbar region.